2005
DOI: 10.1111/j.1551-2916.2005.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Whisker β‐Spodumene Glass–Ceramics

Abstract: β‐spodumene glass–ceramics with a whisker‐like microstructure were prepared from the following materials (in wt%): 64.5 SiO2, 18.0 Al2O3, 4.2 Li2O, 4 ZrO2, and 8 MgF2. Scanning electron microscope (SEM) analysis showed that phase separation in the base glass leads to the formation of a primary crystal phase of MgF2 that promotes the formation of spherical β‐spodumene. Whisker spodumene crystals surrounded by spherical crystals are observed at 720°C after 1 h, and the whisker crystals grow at the cost of spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…have demonstrated an increase in the flexural strength with the crystal size of such a microstructure of interlocked whisker‐shaped β‐spodumene crystals. In analogy with the material of Anmin et al . we believe that the reinforcement contribution associated with the morphology of the crystals embedded in the glassy matrix is significant in our proposed LAS‐glass‐ceramic as well.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…have demonstrated an increase in the flexural strength with the crystal size of such a microstructure of interlocked whisker‐shaped β‐spodumene crystals. In analogy with the material of Anmin et al . we believe that the reinforcement contribution associated with the morphology of the crystals embedded in the glassy matrix is significant in our proposed LAS‐glass‐ceramic as well.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, the coefficient of thermal expansion (CTE) of β‐spodumene is 1–3 × 10 −6 K −1 , whereas Li 2 Si 2 O 5 exhibits a CTE of ~9 × 10 −6 K −1 . From a micromechanical point of view we presume that the presence of these two crystalline phases of very different CTEs in a glassy matrix generate a compressive stress state upon cooling, therefore imparting superior flexural strength compared to strengths of LAS‐glass‐ceramics reported in the literature. These preliminary investigations have also shown that microstructure as well as heating scheme is decisive for tailoring the mechanical properties and the esthetics of the glass‐ceramic.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…13 samples have not been treated by laser but were crystallized with the same temperature profile to get a reference value. Anmin et al [17] have observed that an increase of the flexural strength depends on the size of these interlocked whisker-shaped β-spodumene crystals. By locally increasing the length and size of this β-spodumene crystal through laser radiation, an effect on the flexural strength is expected to be visible.…”
Section: Laser-induced Modificationsmentioning
confidence: 99%